CONTEMPORARY FEATURES OF COOPERATION BETWEEN RUSSIA AND KAZAKHSTAN IN HIGHER EDUCATION - Burangulov, E.R. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Mezhdunarodnye otnosheni͡a, 2017)
The article reveals and compares the features and trends of the public policy in the sphere of higher education in Russia and Kazakhstan on the materials of programs, concepts, regulations and speeches of officials in the sphere of educational cooperation. The general factors defining orientation of such inter-action (following to the Bologna agreement and orientation to reconstruction of uniform educational space) and also particular factors are allocated (decentralization and aspiration to nation-building in Kazakhstan, centralization of an education system in Russia). Such problem as transformation of the Bologna system into the channel of recruiting by the leading countries of the most successful and perspective university graduates of Russia and Kazakhstan is accented. The main bilateral educational projects are considered: Network University of the CIS and University of the Shanghai Cooperation Organization. Two main conclusions are drawn. First, that orientation to the Bo-logna system became the response to changes of social installations and economic situation in the world. Second, such development and the actual strategies of public policy in the sphere of educational cooperation need to be adjusted in accordance with national traditions with the aim of preserving and enhancing the ac-cumulated intellectual, scientific and technical, cultural potential and sustainable socio-political development of Russia and Kazakhstan.